The Absorption Characteristics of Nonvolatile Components in a Water Extraction From Amomi fructus as Determined by In Situ Single-Pass Intestinal Perfusion and High-Performance Liquid Chromatography - Yao, Yuebao; Mi, Wenjuan; Cao, Guangzhao; Yang, Ruiqi; Chen, Huirong; Liu, Yong; Zou, Huiqin; Yan, Yonghong (Frontiers in Pharmacology, 2020)
Background: Amomi Fructus (A. Fructus) is a famous traditional Chinese medicine (TCM), with beneficial effects on treating gastrointestinal diseases and wide application in China and other countries in Southeast Asia. However, its non-volatile active ingredients from water extraction for treating gastric diseases remain unclear. The goal of this study was to explore the non-volatile active ingredients of A. Fructus. Methods: The In suit single-pass intestinal perfusion (SPIP) model was applied to explore the active ingredients of A. Fructus, which play significant roles in gastrointestinal absorption. A performance liquid chromatography (HPLC) method was developed and further validated for simultaneous determination of intestinal outflow perfusate. Results: Nineteen indexes in the water extraction from A. Fructus possessed different absorption abilities in different intestinal segments. Among them six components were determined by the developed standards, namely, catechin, vanillic acid, epicatechin, polydatin, isoquercitrin and quercitrin. Conclusions: The current study preliminarily explored the active ingredients from the water extraction of A. Fructus in the single-intestinal perfusate of rats and provided experimental basis for explaining the pharmacodynamic basis of A. Fructus.